Resident human dermal γδT-cells operate as stress-sentinels: Lessons from the hair follicle. Issue 124 (November 2021) - Uchida, Youhei; Gherardini, Jennifer; Pappelbaum, Karin; Chéret, Jérémy; Schulte-Mecklenbeck, Andreas; Gross, Catharina C.; Strbo, Natasa; Gilhar, Amos; Rossi, Alfredo; Funk, Wolfgang; Kanekura, Takuro; Almeida, Luís; et al.
Abstract: Murine γδT-cells have stress-surveillance functions and are implicated in autoimmunity. Yet, whether human γδT-cells are also stress sentinels and directly promote autoimmune responses in the skin is unknown. Using a novel (mini-)organ assay, we tested if human dermis resident γδT-cells can recognize stressed human scalp hair follicles (HFs) to promote an alopecia areata (AA)-like autoimmune response. Accordingly, we show that γδT-cells from healthy human scalp skin are activated (CD69 + ), up-regulate the expression of NKG2D and IFN-γ, and become cytotoxic when co-cultured with autologous stressed HFs ex vivo . These autologous γδT-cells induce HF immune privilege collapse, dystrophy, and premature catagen, i.e. three hallmarks of the human autoimmune HF disorder, AA. This is mediated by CXCL12, MICA, and in part by IFN-γ and CD1d. In conclusion, human dermal γδT-cells exert physiological stress-sentinel functions in human skin, where their excessive activity can promote autoimmunity towards stressed HFs that overexpress CD1d, CXCL12, and/or MICA. Highlights: Human γδT-cells are stress sentinels. Stressed hair follicles recruit and activate human γδT-cells. Autologous γδT-cells promote alopecia areata-like autoimmunity towards stressed hair follicles. Hair follicle cultures are a valuable tool to study skin-human γδT-cell crosstalk.